1985
DOI: 10.1111/j.1365-2427.1985.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipids as feeding stimulants for shredding aquatic insects

Abstract: 1. Caddisflies (Trichoptera) that shred leaf detritus preferentially ingested lipid-coated detritus during the last larval instar. This is the interval when these insects accumulate the triglyceride reserves necessary for metamorphosis and reproduction. Early instar larvae, which do not accumulate lipids, showed no preference for any lipids. This behaviour indicates food selection based on changing nutritional needs.2. Pure unsaturated 18-and 20-carbon fatty acids, either as free acids or triglycerides, were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…PV So8 did not attract G. roeselii but rather repelled the gammarid, leads us to conclude that compounds other than those extracted by methanol mediate the preference. The food selection of aquatic insects is influenced by their nutritional needs because their food often contains low amounts of available proteins, carbohydrates, and lipids (CARGILL et al, 1985a). CARGILL et al (1985a) showed that five Trichoptera species preferred leaf discs coated with pure unsaturated 18-and 20-carbon fatty acids, which suggests that lipids from aquatic hyphomycetes are important intermediates in the energy transfer from detritus to detritivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PV So8 did not attract G. roeselii but rather repelled the gammarid, leads us to conclude that compounds other than those extracted by methanol mediate the preference. The food selection of aquatic insects is influenced by their nutritional needs because their food often contains low amounts of available proteins, carbohydrates, and lipids (CARGILL et al, 1985a). CARGILL et al (1985a) showed that five Trichoptera species preferred leaf discs coated with pure unsaturated 18-and 20-carbon fatty acids, which suggests that lipids from aquatic hyphomycetes are important intermediates in the energy transfer from detritus to detritivores.…”
Section: Discussionmentioning
confidence: 99%
“…The food selection of aquatic insects is influenced by their nutritional needs because their food often contains low amounts of available proteins, carbohydrates, and lipids (CARGILL et al, 1985a). CARGILL et al (1985a) showed that five Trichoptera species preferred leaf discs coated with pure unsaturated 18-and 20-carbon fatty acids, which suggests that lipids from aquatic hyphomycetes are important intermediates in the energy transfer from detritus to detritivores. Lipid extracts of three aquatic hyphomycetes led to the same patterns of leaf consumption by Gammarus tigrinus as leaf litter inoculated with those fungi (RONG et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we measured the energy reserves by assaying glycogen and lipid contents. Glycogen represents a short-term energy source available for current activities (Sparkes et al, 1996), whereas lipids are used for long-term storage to be used as nutrients during starvation or reproduction periods (Cargill et al, 1985). Finally, we measured the levels of malondialdehyde (MDA), a product of lipid peroxidation considered as a toxicity biomarker which reflects cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, energy reserves were estimated by measuring protein concentrations as well as total lipid and glycogen contents. The levels of glycogen are representative of the energy available for current activities (Sparkes et al, 1996) whereas lipids are stored in fat bodies and are used during starvation or reproduction periods (Cargill et al, 1985).…”
Section: Introductionmentioning
confidence: 99%